2021
DOI: 10.3389/fnins.2021.704079
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Lobe Reorganization and Widespread Functional Connectivity Integration in Upper-Limb Amputees: A rs-fMRI Study

Abstract: The right parietal lobe plays an important role in body image, and disorders of body image emerge after lesions in the parietal lobe or with parietal lobe epilepsy. Body image disorder also often accompanies upper-limb amputation, in which the patient misperceives that their missing limb is still part of their body. Cortical reorganization is known to occur after upper-limb amputation, but it is not clear how widespread and to what degree functional connectivity (FC) is reorganized post-amputation, nor whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…In our previous studies, both functional connectivity and functional brain network analyses demonstrated that significant changes also occur in this region 12,13 . These findings from this study provide further evidence supporting the coupling of function and structure, which will guide us in future studies of the CRT after amputation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In our previous studies, both functional connectivity and functional brain network analyses demonstrated that significant changes also occur in this region 12,13 . These findings from this study provide further evidence supporting the coupling of function and structure, which will guide us in future studies of the CRT after amputation.…”
Section: Discussionsupporting
confidence: 78%
“…In our previous studies, both functional connectivity and functional brain network analyses demonstrated that significant changes also occur in this region. 12 , 13 These findings from this study provide further evidence supporting the coupling of function and structure, which will guide us in future studies of the CRT after amputation. Interestingly, our correlation analysis with clinical manifestations showed that the decrease in CTh was negatively correlated with PLP score, which suggests that lower CTh was associated with more intense PLP.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations